NICKNAMING AS A MORPHOLOGICAL AND LEXICO-SEMANTIC PROCESS: IMPLICATION FOR LANGUAGE LEARNING AND TEACHING - Ugwu, Esther Nkiruka; Ekundayo, Steve Bode O. (European Scientific Journal, ESJ, 2013)
Many morphological processes and sociolinguistic sources pour words into language. However, nicknaming is one rich source of word creation not often stressed in the discussion of morphological and lexico-semantic processes. This paper looks at the phenomenon of nicknaming and submits that it is a veritable morpho-semantic process. Examples are drawn from two historically related languages: Nigerian Pidgin (NP), on the one hand, and Nigerian English (NE) varieties, on the other hand. Through the observation of linguistic events and library research conducted from 2008 to 2011, this paper shows that many words and lexical meanings pour into NP and NE varieties by the instrumentality of nicknaming. Nigerian nickname things, places and people to praise, understate, overstate, avoid vulgarity and indecency, insult and tease in all the spheres of life. In doing these, they generate new words and meanings.